Season-to-season variations of physiological fitness within a squad of professional male soccer players - Clark, N. A.; Edwards, A. M.; Morton, R. H.; Butterly, R. J. (Journal of Sports Science & Medicine, 2008)
The purpose of this study was to examine season-to-season variations in physiological fitness parameters among a 1st team squad of professional adult male soccer players for the confirmatory purposes of identifying normative responses (immediately prior to pre-season training (PPS), mid-season (MID), and end-of-season (EOS)). Test-retest data were collected from a student population on the primary dependent variables of anaerobic threshold (AT) and maximal aerobic power (VO2 max) to define meaningful measurement change in excess of test-retest technical error between test-to-test performances. Participants from a pool of 42 professional soccer players were tested over a set sequence of tests during the 3-year period: 1) basic anthropometry, 2) countermovement jump (CMJ) tests 3) a combined AT and VO2 max test. Over the 3-year period there were no test-to-test changes in mean VO2 max performance exceeding pre-defined limits of test agreement (mean of eight measures: 61.6 ± 0.6 ml·kg-1·min-1). In contrast, VO2 at AT was significantly higher at the MID test occasion in seasons 2 (+4.8%; p = 0.04, p < 0.05) and 3 (+6.8%; p = 0.03, p < 0.05). The CMJ tests showed a test-to-test improvement of 6.3% (best of 3 jumps) (p = 0.03, p < 0.05) and 10.3% (20-s sustained jumping test) (p = 0.007, p < 0.01) between PPS2 and MID2 and thereafter remained stable. Anthropometrics were unaffected. In summary, despite some personnel changes in the elite cohort between test-to-test occasions, VO2 max values did not vary significantly over the study which supports previous short-term observations suggesting a general 'elite' threshold of 60 ml·kg-1 min. Interestingly, AT significantly varied where VO2 max was stable and these variations also coincided with on- and off-seasons suggesting that AT is a better indication of acute training state than VO2 max.